Bone Mineral Density in Iranian Kidney Graft Recipients and Its Relation to Biochemical and PTH Serum Levels - M Mahdavi; Z Hamidi; A Soltani; M Sedaghat; M Lessan- Pezeshki; B Larijani (Tehran University of Medical Sciences, 2004)
Little is known about relation of transplantation and bone. We conducted a study to find out the frequency and predictors of osteoporosis in kidney transplanted patients in Iran. DEXA (DPX-MD, GE, Lunar corporation, USA) used for BMD of 61 kidney transplanted patients. Calcium, phosphate, alkaline phosphatase, BUN, creatinine and PTH, were also measured. Fourty four percent of patients were men (27). Mean±SD of age of men and women was 44.3±10.44 and 40/7± 13.77, respectively. Mean±SD of transplant duration was 33.9± 33. 2 months Mean±SD of dialysis time was 12±14 months. 29.5% of patients had osteoporosis. Osteoporosis was significantly higher in subjects with BMI less than 19 kg/m2 (P= 0.007). Alkaline phosphatase had a negative relation with osteoporosis in neck (P= 0.001). Other parameters had no significant relationship with osteoporosis. High prevalence of osteoporosis found in Iranian kidney graft recipients. Screening and therapeutic intervention in these patients is urgently needed.